Annual concentrations of thyroxin and progesterone in Karagouniko and Chios ewes - KANTAS (Δ. ΚΑΝΤΑΣ), D.; VALASI (Ε. ΒΑΛΑΣΗ), E.; TSILIGIANNI (Θ. ΤΣΙΛΙΓΙΑΝΝΗ), Th.; NTOVOLOU (Ε. ΝΤΟΒΟΛΟΥ), E.; RIGAS (Γ. ΡΗΓΑΣ), G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The circannual secretion of progesterone and thyroxin of two indigenous sheep breeds (Chios and Karagouniko, each n=10) with different reproductive pattern was investigated. Blood samples were collected weekly and the serum hormone's concentration was assayed by RIA. Between breeds, no difference was detected in the mean annual thyroxin concentration. Similarly, no differences were detected within breeds in the mean thyroxin concentrations for the periods of increasing and decreasing daylight. Clear thyroxin peaks were detected in both breeds a month or so prior to the transition to anestrus period; these peaks were higher in the Karagouniko breed. Breeding season duration was clearly shorter in Karagouniko in comparison with that of Chios; in the later breed many animals had substantially short anestrus. These results give strong indications that thyroid activity has a catalytic role in the regulation of the reproductive period in ewes.